The Multifarious Functions of Leukotrienes in Bone Metabolism - Amadeu de Oliveira, Flávia (2023)
Leukotrienes (LTs) are derived from arachidonic acid metabolism by the 5-lipoxygenase (5-LO) enzyme. The production of LTs is stimulated in the pathogenesis of rheumatoid arthritis (RA), osteoarthritis, and periodontitis, with a relevant contribution to bone resorption. However, its role in bone turnover, particularly the suppression of bone formation by modulating the function of osteoclasts and osteoblasts, remains unclear. We investigated the effects of LTs on bone metabolism and their impact on osteogenic differentiation and osteoclastogenesis using a 5-LO knockout (KO) mouse model. Results from micro-computed tomography (μCT) analysis of femur from 8-week-old 5-LO-deficient mice showed increased cortical bone and medullary region in females and males and decreased trabecular bone in females. In the vertebra, we observed increased marrow area in both females and males 5-LO KO and decreased trabecular bone only in females 5-LO KO. Immunohistochemistry (IHC) analysis showed higher levels of osteogenic markers tissue-nonspecific alkaline phosphatase (TNAP) and osteopontin (OPN) and lower expression of osteoclastogenic marker tartrate-resistant acid phosphatase (TRAP) in the femurs of 5-LO KO mice versus wild-type (WT). Alkaline phosphatase activity and mineralization assay results showed that the 5-LO absence enhances osteoblasts differentiation and mineralization but decreases the proliferation. Alkaline phosphatase (ALP), Bglap, and Sp7 gene expression were higher in 5-LO KO osteoblasts compared to WT cells. Eicosanoids production was higher in 5-LO KO osteoblasts except for thromboxane 2, which was lower in 5-LO–deficient mice. Proteomic analysis identified the downregulation of proteins related to adenosine triphosphate (ATP) metabolism in 5-LO KO osteoblasts, and the upregulation of transcription factors such as the adaptor-related protein complex 1 (AP-1 complex) in long bones from 5-LO KO mice leading to an increased bone formation pattern in 5-LO–deficient mice. We observed enormous differences in the morphology and function of osteoclasts with reduced bone resorption markers and impaired osteoclasts in 5-LO KO compared to WT osteoclasts. Altogether, these results demonstrate that the absence of 5-LO is related to the greater osteogenic profile. © 2023 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).